Realization of Students’ Academic Rights: Russia in the Bologna Process - G. M. Romanova; V. P. Erdakova; M. A. Maznichenko (Высшее образование в России)
The article considers the existing practice of realizing students’ academic rights in Russia in comparison with foreign countries (USA, European Union) and in the context of the key principles of the Bologna process (quality assurance, use of the credit system (ECTS), increased mobility, lifelong learning, student-centeredness, social dimension and social accessibility). The article dwells on the features of the domestic practice of the implementation of students’ academic rights distinct from the European and the United States, including those associated with different traditions of legal regulation and different mentality of participants in educational relations. The following conclusions were made: (1) the composition of academic rights, their legislative regulation and the practice of implementation in Russia and abroad have significant differences; (2) as compared with foreign students, Russian students are less active in exercising and defending their academic rights; (3) in the Russian practice of exercising academic rights there is a number of problems that do not allow the full implementation of the principles of the Bologna process; (4) for the full implementation of these principles, it is necessary to improve the domestic practice of the implementation of students’ academic rights.